ATTRIBUTES OF ACIDITY AND EXCHANGEABLE CATIONS IN OXISOL FERTILIZED BY PHOSPHATE ALKALINE BIOSOLID ATRIBUTOS DE ACIDEZ E CÁTIONS TROCÁVEIS EM LATOSSOLO FERTILIZADO POR BIOSSÓLIDO ALCALINIZADO FOSFATADO - SILVA, Luiz Carlos DA; Corrêa LUCCHESI, Luiz Antonio; Soares KOEHLER, Henrique (Scientia Agraria, 2011)
ABSTRACT Alkaline biosolid enriched by phosphorus (P) increase soil extractable P more than applied alone. It also can exert further effects above soil acidity attributes and exchangeable calcium and magnesium. These facts can contribute to the solution of problems with final destination, attracting farmers to use of adequate quantities of these biosolids by reducing his costs with P fertilization and liming operations. The objective of this work was to evaluate the acidity attributes pH (CaCl2 0.01 mol dm-3), exchangeable aluminum, potential acidity and exchangeable calcium and magnesium on an acidic Oxisol fertilized with alkaline biosolid phosphated with different levels of phosphorus from three sources after common bean grown under greenhouse condition. An alkaline biosolid was phosphate with 0% P, 0.436% P, 0.872% P and 1.745% P from partially acidulated rock phosphate Alvorada, single superphosphate and triple superphosphate. To stablish the treatments was recommended 45.85 kg P ha-1 of P from the levels of P added, except from 0% P. Four levels and 3 sources of P generated 12 treatments with 4 replications. Treatments were applied to 2.5 kg dry weight of Oxisol from Arapoti, PR, Brazil, in vases, which was cultivated with 6 common bean plants (cv. IPR Uirapuru). Under these experimental conditions phosphate alkaline biosolid applied in acidic Oxisol provided the largest increases of soil pH, exchangeable calcium and magnesium and decreases in exchangeable aluminum and potential acidity with the level of 0.436% P from the partially acidulated rock phosphate Alvorada and single superphosphate. RESUMO Biossólido alcalinizado enriquecido com fósforo (P) aumenta o P extraível mais do que aplicado sozinho. Também pode exercer efeitos adicionais sobre os atributos de acidez e cálcio e magnésio trocáveis do solo. Estes fatos podem contribuir para solução de problemas de destinação final, atraindo produtores à utilização de quantidades adequadas destes biossólidos por reduzir seus custos com adubação e correção de solos. O objetivo deste trabalho foi avaliar os atributos de acidez pH (CaCl2 0,01 mol dm-3), alumínio trocável, acidez potencial e cálcio e magnésio trocáveis em Latossolo fertilizado com biossólido de esgoto alcalinizado fosfatado com diferentes níveis de fósforo de três fontes após o cultivo de feijoeiro comum em casa de vegetação. Um biossólido alcalinizado foi fosfatado com 0% P, 0,436% P, 0,872% P e 1,745% P de fosfato natural parcialmente acidulado Alvorada, superfosfato simples e superfosfato triplo. Para estabelecer os tratamentos recomendou-se 45,85 kg ha-1 de P a partir dos níveis de P adicionado, exceto do nível 0% P. Quatro níveis e 3 fontes de P adicionado geraram 12 tratamentos com 4 repetições. Os tratamentos foram aplicados a 2,5 kg de Latossolo Vermelho Distrófico típico, ácido, em vasos cultivados com 6 plantas de feijoeiro (cv. IPR Uirapuru). Sob estas condições experimentais biossólido de esgoto alcalinizado fosfatado proporcionou os maiores aumentos de pH do solo e cálcio e magnésio trocáveis e diminuições do alumínio trocável e acidez potencial com o nível de 0.436% P de fosfato natural parcialmente acidulado Alvorada e superfosfato simples.